T cell deficiency in spinal cord injury: altered locomotor recovery and whole-genome transcriptional analysis. Issue 1 (December 2015) - Satzer, David; Miller, Catherine; Maxon, Jacob; Voth, Joseph; DiBartolomeo, Christina; Mahoney, Rebecca; Dutton, James; Low, Walter; Parr, Ann
Abstract Background T cells undergo autoimmunization following spinal cord injury (SCI) and play both protective and destructive roles during the recovery process. T cell-deficient athymic nude (AN) rats exhibit improved functional recovery when compared to immunocompetent Sprague–Dawley (SD) rats following spinal cord transection. Methods In the present study, we evaluated locomotor recovery in SD and AN rats following moderate spinal cord contusion. To explain variable locomotor outcome, we assessed whole-genome expression using RNA sequencing, in the acute (1 week post-injury) and chronic (8 weeks post-injury) phases of recovery. Results Athymic nude rats demonstrated greater locomotor function than SD rats only at 1 week post-injury, coinciding with peak T cell infiltration in immunocompetent rats. Genetic markers for T cells and helper T cells were acutely enriched in SD rats, while AN rats expressed genes for Th 2 cells, cytotoxic T cells, NK cells, mast cells, IL-1a, and IL-6 at higher levels. Acute enrichment of cell death-related genes suggested that SD rats undergo secondary tissue damage from T cells. Additionally, SD rats exhibited increased acute expression of voltage-gated potassium (Kv ) channel-related genes. However, AN rats demonstrated greater chronic expression of cell death-associated genes and less expression of axon-related genes. Immunostaining for macrophage markers revealed no T cell-dependent difference in the acute macrophage infiltrate. Conclusions We put forth a model in which T cells facilitate early tissue damage, demyelination, and Kv channel dysregulation in SD rats following contusion SCI. However, compensatory features of the immune response in AN rats cause delayed tissue death and limit long-term recovery. T cell inhibition combined with other neuroprotective treatment may thus be a promising therapeutic avenue.